2020
DOI: 10.1002/app.49564
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of graded microporous layers for enhanced water management in fuel cells

Abstract: The newly prepared gas diffusion layer (GDL) was studied in this article. The new GDL mainly includes a carbon paper layer and two microporous layers (MPLs) on the same side of carbon paper. The two MPLs were fabricated by using conductive carbon blacks of two different carbon morphology, Vulcan XC‐72, and acetylene black carbon, respectively. From the results of the water contact angle and conductivity, it was found that the GDL prepared by spraying has not only good hydrophobicity but also low resistivity. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Lin et al [94] prepared a gradient double-layer MPL structures by using conductive carbon black with different particle size, so as to achieve gradual change of pore size from GDL to CL, with the aim to improve the water management ability. They therefore designed a GDL with an MPL containing two layers that were different in pore size (as shown in Figure 9a) by using two types of conductive carbon blacks-one is acetylene carbon black (7-20 µm), the other is Vulcan XC-72 (20-100 µm).…”
Section: Structural Parameters For Gdl 61 Pore Structurementioning
confidence: 99%
“…Lin et al [94] prepared a gradient double-layer MPL structures by using conductive carbon black with different particle size, so as to achieve gradual change of pore size from GDL to CL, with the aim to improve the water management ability. They therefore designed a GDL with an MPL containing two layers that were different in pore size (as shown in Figure 9a) by using two types of conductive carbon blacks-one is acetylene carbon black (7-20 µm), the other is Vulcan XC-72 (20-100 µm).…”
Section: Structural Parameters For Gdl 61 Pore Structurementioning
confidence: 99%
“…In addition, MPLs with a porosity gradient experience internal capillary pressure. Similarly, other researchers have shown that MPLs with a porosity gradient introduced using ammonium chloride exhibit electrochemical performance superior to that of MPLs with a uniform pore-size distribution. The addition of thermally expandable GPs has been reported as another approach for the fabrication of MPLs with a porosity gradient . MPLs with gradient hydrophobicity have also been effective for draining water accumulated in GDLs .…”
Section: Introductionmentioning
confidence: 97%
“…MPLs with gradient hydrophobicity have also been effective for draining water accumulated in GDLs . To fabricate MPLs with gradient features requires at least one step of the wet-coating process to be repeated. ,, However, repeated drying and annealing processes for the fabrication of multilayers significantly increase the product cost and the environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“…11,16 The introduction of polymer hydrophobic agents into the MPL is beneficial for the water drainage. 17 However, this physical mixing method is deficient on several levels. First, due to the difference in surface physical properties and solubility in solvents between the carbon matrix elements and the hydrophobic agents, they tend to agglomerate individually and undergo phase separation, resulting in an inhomogeneous distribution of hydrophobic agents in the mixture and cannot avoid water flooding of the electrode efficiently.…”
Section: Introductionmentioning
confidence: 99%